IDENTIFICATION OF THE PART OF THE SENSES AND THEIR AUXILIARY ORGANS IN AIDING HUMAN ACTIVITIES - Rizka Veronika Kidam (Jurnal Ilmiah dr. Aloei Saboe, 2023)
Each individual is created with a complete sense system that is used to be able to interact with the surrounding environment, which can be obtained through the senses, namely the eyes, ears, nose, tongue, and skin. DestinationThis study aims to determine the parts of the senses and their complementary organs that help human activities. The method used in this research is the experimental method, the experimental method is an action and observation or testing a hypothesis. Experiments can be carried out in a laboratory or outside the laboratory, experimental work implies learning to do, because it can be included in the learning method. The results of the research on taste sensitivity showed that the results obtained for the first probandus for the garlic sample contained 1 guessing error, while for the onion sample there were 2 guessing errors, for the apple sample all were correct. The second proband for the garlic sample was all answered, the onion contained an error 1 while the apples were all correct. In this blind spot study, we found differences in the distance of the blind spots in one proband to another. This is because the size of the eyeball, the convexity of the eye lens and the distance from the lens to the retina are different for each person.